EEG Beta Oscillations in the Temporoparietal Area Related to the Accuracy in Estimating Others' Preference - Park, Jonghyeok; Kim, Hackjin; Sohn, Jeong-Woo; Choi, Jong-ryul; Kim, Sung-Phil (Frontiers in Human Neuroscience, 2018)
Humans often attempt to predict what others prefer based on a narrow slice of experience, called thin-slicing. According to the theoretical bases for how humans can predict the preference of others, one tends to estimate the other’s preference using a perceived difference between the other and self. Previous neuroimaging studies have revealed that the network of dorsal medial prefrontal cortex (dmPFC) and right temporoparietal junction (rTPJ) is related to the ability of predicting others’ preference. However, it still remains unknown about the temporal patterns of neural activities for others’ preference prediction through thin-slicing. To investigate such temporal aspects of neural activities, we investigated human electroencephalography (EEG) recorded during the task of predicting the preference of others while only a facial picture of others was provided. Twenty participants (all female, average age: 21.86) participated in the study. In each trial of the task, participants were shown a picture of either a target person or self for three seconds, followed by the presentation of a movie poster over which participants predicted the target person’s preference as liking or disliking. The time-frequency EEG analysis was employed to analyze temporal changes in the amplitudes of brain oscillations. Participants could predict others’ preference for movies with accuracy of 56.89 ± 3.16 % and ten out of twenty participants exhibited prediction accuracy higher than a chance level (95% interval). There was a significant difference in the power of the parietal alpha (10~13Hz) oscillation 0.6 ~ 0.8s after the onset of poster presentation between the cases when participants predicted others’ preference and when they reported self-preference (p < 0.05). The power of brain oscillations at any frequency band and time period during the trial did not show a significant correlation with individual prediction accuracy. However, when we measured differences of the power between the trials of predicting other’s preference and reporting self-preference, the right temporal beta oscillations 1.6 ~ 1.8s after the onset of facial picture presentation exhibited a significant correlation with individual accuracy. Our results suggest that right temporoparietal beta oscillations may be correlated with one’s ability to predict what others prefer with minimal information.